A Comparative Analysis of the Pathogenesis of Plasmodium vivax and Plasmodium falciparum: A Literature Review - Anak Agung Ngurah Ardha Dwikananda; Dewa Ayu Agus Sri Laksemi; Putu Ayu Asri Damayanti (International Medical Journal Corp. Ltd, 2025)
Background: Malaria is one of the significant health problems faced in the world with Plasmodium falciparum and Plasmodium vivax being the major two types of malaria in humans. Humans have long been exposed to plasmodium falciparum, which causes severe disease with dangerous complications, compared to plasmodium vivax, which was identified as causing a less severe, relapsing infection. But recent data casts doubt on this dichotomy since there is the possibility of P. vivax causing severe, and even fatal forms of malaria. Objective: The objective of this review is to compare the pathogenic processes of Plasmodium falciparum and Plasmodium vivax systematically in terms of molecular, cellular interactions, host immunity aspects with the associated clinical presentation and morbidities. Methods: Search of the literature was carried at PubMed, Scopus, and Google Scholar databases with the use of pathogenesis, clinical characteristic and complications of both species to be compared. Results: Literature synthesis indicates that there are unique pathogenic profiles. Major dissimilarities were established in path of erythrocyte invasion, accomplishment of cytoadherence and sequestration, alteration of the host cell, and potential biomass of the parasite. The pathogenesis of the Plasmodium falciparum generally involves microvascular obstruction due to sequestration whereas the pathology of Plasmodium vivax seems more to do with the excessive inflammatory status, severe anaemia and complications of the parasite unique life cycle stages that have evolved as hypnozoites. Conclusion: The causes of infections are different, but both species are serious pathogens that can bring serious illnesses. An in-depth consideration of their specific and symbiotic virulence mechanisms is extremely important in making progress in clinical practice, diagnostics, and creation of new customized therapies and prophylaxis.